RELATIVELY CANCELLATION MODULES - Mahmood, Layla S; Shihab, Bothaynah N; Rasheed, Thair S (Al-Nahrain Journal of Science, 2010)
Let R be a commutative ring with identity and M be unitary (left) R-module. We shall introducethe concepts of relatively cancellation modules (weakly relatively cancellation modules.Clearly, the class of weakly relatively cancellation modules contains the class of relativelycancellation modules.The principal aim of this paper is to study in some details these two concepts. We givenecessary and (or) sufficient for these two types of modules to be equivalent